Pengaruh Laba Akuntansi, Komponen Arus Kas dan Dividend Yield Terhadap Return Saham - Abdillah Arif Nasution; Endi Rustendi; Julie Theresya Pelamonia; Made Susilawati; Musran Munizu (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze and determine the Effect of Accounting Profit, Cash Flow Components, and Dividend Yield on Stock Returns. The research method used in this study is a descriptive statistical method. With verification testing using multiple regression (multiple regression). The data used is secondary data, namely the annual report of the company that was used as a sample in the study. The research sample was 12 companies listed on the Indonesia Stock Exchange in 2020-2023 which were taken using the purposive sampling method. The results of this study indicate that Accounting Profit, Operating Cash Flow, Investment Cash Flow, Funding Cash Flow, and Dividend Yield have a positive and significant effect on Stock Returns.